Recovery of Household Consumption as Accelerator of Economic Recovery in East Java: Empirical Study and Macro Policy Strategies - Muhamad Fathul Muin (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2022)
The Covid-19 pandemic has harmed the economy in East Java. Households with the largest share of RGDP also experienced sluggish demand, which impacted the economic decline in East Java of more than eight trillion rupiahs. Economic recovery efforts through household consumption recovery are one of the strategic options to accelerate general economic recovery. Therefore, this study was conducted on RGDP data for household expenditure groups in all districts/cities in East Java during the 2016-2020 period using a panel regression analysis approach. The variables used include household consumption GRDP growth, inflation, regional poverty profile, percentage of internet users for online shopping, and the realization of social spending per capita of the poor. The findings of this study indicate that household consumption in East Java is classified as inelastic to price changes. It is due to the dominance of food consumption and controlled inflation. Meanwhile, the regional poverty profile has a negative impact on the recovery of household consumption. It shows that districts/cities with a high percentage of poor people tend to be more difficult to recover. Furthermore, the digitalization of the economy through e-commerce has not yet had a significant effect on the recovery of household consumption. It is due to the low use of the internet for online shopping among the population. The realization of social assistance per capita has a positive effect in encouraging the recovery of household consumption, although the contribution given is relatively small. It is caused by the low social assistance received compared to the loss of income experienced by the community. As a follow-up, there are four policies that the government can take to encourage the recovery of household consumption, including the sustainability of food price stabilization policies, increased penetration and digital education for MSMEs and the public, a combination of massive and comprehensive poverty alleviation policies, and synchronization of fiscal policy between government level.